PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA DAN SIKAP SISWA MELALUI MODEL PEMBELAJARAN KONTRUKTIVISME (STUDI EKSPERIMEN KUASI PADA SEKOLAH DASAR) - Faqih Hakim Hasibuan (Studi Multidisipliner: Jurnal Kajian Keislaman, 2017)
Reading skills are skills that are very unique and important role for the development of knowledge. He also as a communication tool for human life. Teaching reading is probably the most effective teaching of reading is based on a good understanding of the reading process itself and which encourage mastery of reading strategies appropriate, but it must be admitted that there is no definition of the most appropriate.